PENGARUH MEDIA SOSIAL TERHADAP HASIL BELAJAR PENDIDIKAN AGAMA KATOLIK SISWA KELAS VIII DI SMP SANTA MARIA PALANGKA RAYA TAHUN PEMBELAJARAN 2020/2021 - Maria Eupaharasia Sena Bha; Paulina Maria. E.W; Romanus Roman (Sepakat : Jurnal Pastoral Kateketik, 2021)
This study aims to determine the effect of social media on learning outcomes in PAK (Catholic religious education) learning at Santa Maria Palangka Raya Middle School, especially for class VIII students. Through this research, the researcher wants to see further whether there is an influence of social media on the learning outcomes of Catholic Religious Education. This study uses a quantitative approach. The research location is at St. Catholic Junior High School. Maria Palangka Raya. The research population is all students in class VIII. The research sample is class VIII B and C taken by cluster random sampling technique. Data collection techniques used questionnaires distributed via google form and additional interviews with Catholic religious education teachers. The data analysis technique used Pearson's product moment correlation technique.